Del periodista pasible, la obviedad informativa y otras confusiones en el Estanco de Noticias - Dader, José Luis (Estudios sobre el Mensaje Periodístico, 2007)
The contemporary theory of journalism is still lacking a thoughtful epistemological foundation. The abandonment of objectivity as a key value of journalism has provoked the lessening of professional standards and the returning of political passions as the main criteria for current news coverage. Ideologically biased information has saturated the audiences and “soft news” and “infotainment” have flourished as the only counterpoint. The distortion of journalism by the plain delivery of rumors and sectarian political criticism compels the professionalism in journalism to seek a philosophical empowerment. Objectivity, careful verification and a detached search of truth is coming back as the key elements of a responsible contribution of journalism to the civic consciousness within the democratic societies.